Plasma apelin and vascular endothelial growth factor levels in preterm infants: relationship to neonatal respiratory distress syndrome. (12th December 2022) - Zhang, Yimin; Shao, Shuming; Mu, Qing; Feng, Jing; Liu, Jie; Zeng, Chaomei; Qin, Jiong; Zhang, Xiaorui
Abstract: Aim: The study aimed to determine the association between cord plasma levels of apelin and vascular endothelial growth factor (VEGF) with respiratory distress syndrome (RDS) in preterm infants. Methods: This case-control study included 120 preterm infants admitted to the neonatal intensive care unit of our hospital between January 2019 and January 2020. The infants were divided into RDS ( n  = 60) and non-RDS groups ( n  = 60). The cord plasma apelin and VEGF levels, perinatal characteristics, and neonatal complications were compared between the two groups. Results: The plasma apelin levels in the RDS group were significantly higher than in the non-RDS group (158.9 ± 24.8 vs. 125.2 ± 18.2 pg/mL, respectively), whereas VEGF levels in the non-RDS group were significantly higher than in the RDS group (187.4 ± 28.5 vs. 245.1 ± 44.8 pg/mL, respectively) (both p  < .001). Infants with more severe RDS had higher plasma apelin levels and lower plasma VEGF levels. In the receiver operating characteristic curve analysis for the prediction of RDS, a cutoff of 148.4 pg/mL for apelin level yielded a sensitivity of 63.3% and a specificity of 95.0%, whereas a cutoff of 214.2 pg/mL for VEGF level showed a sensitivity of 86.7% and a specificity of 75.0%. Apelin levels were negatively correlated with VEGF levels in infants with RDS ( r  = 0.84, p  < .001). Conclusion: Differences in cord plasma apelin and VEGF levels may aid in the early diagnosis and treatment of RDS in preterm infants.